(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article highlights the basics of the scientific and practical model of electronic government in the digital economy and provides information about them. The digital economy has a long list of unique features that cannot be found in other types of economies. Free goods and services like Wikipedia, email services like Gmail, and digital maps like Google Maps are all components of the modern digital economy with enormous economic values. However, they cannot contribute to national accounts, as indicators such as GDP only measure the monetary value of all final products at a price (Brynjolfsson and Collis, 2019; Brynjolfsson et al., 2019). In economic terms, this is why we say that the digital economy has produced a ton of very valuable but almost cost-free and zero-marginal-cost services that cannot be captured in standard measures of economic efficiency. In this section, I outline some of the ways in which the digital economy has contributed to improving the economy.